Social Dimensions of Sustainable Development Goals in Asian Countries: Visual Dynamic Research Mapping - Andik Pratama; Juwita Purnami Restu Suwondo; Abdul Rahim Ridzuan; Riska Aprilia (Jurnal Ekonomi Pembangunan, 2025)
As the 2030 deadline for the United Nations’ Sustainable Development Goals (SDGs) approaches, developing Asian nations face critical challenges in balancing economic expansion with the "social pillars" of sustainability. Despite the individual importance of poverty, hunger, health, and education, there remains a gap in understanding their dynamic, integrated interrelationships within the unique institutional and fiscal constraints of the Asian region. This study investigates the dynamic interrelationships among four key social pillars poverty, zero hunger, good health and well-being, and quality education, across 11 developing Asian economies. We employ a robust two-stage methodological approach. First, a systematic bibliometric analysis maps the scholarly landscape and thematic clusters using data from Scopus and Web of Science. Second, an empirical assessment is conducted using a dynamic panel Generalized Method of Moments model on longitudinal data 2017–2023 period to estimate short and long-run effects while addressing endogeneity and heterogeneity. Bibliometric mapping identifies poverty as a central intersectional node bridging healthcare, nutrition, and economics. Empirical results show reveal a strong persistence of poverty, confirming a path-dependent "poverty trap" in the region. While government spending on health and education shows a statistically significant relationship with poverty, its immediate impact is modest, suggesting that public investment effectiveness is often constrained by governance and implementation quality. Furthermore, improvements in neonatal mortality and nutritional status are strongly linked to significant reductions in poverty levels. The findings underscore that poverty, malnutrition, and child mortality are interconnected challenges that cannot be solved through isolated sectoral interventions. Achieving the 2030 Agenda in Asia requires integrated, evidence-based policy frameworks that combine targeted social spending with structural reforms to break intergenerational cycles of deprivation.